Exploring Smart Agents for the Interaction with Multimodal Mediated Environments - Richer, Robert; Zhao, Nan; Eskofier, Björn; Paradiso, Joseph A. (Multimodal Technologies and Interaction, 2020)
After conversational agents have been made available to the broader public, we speculate that applying them as a mediator for adaptive environments reduces control complexity and increases user experience by providing a more natural interaction. We implemented and tested four agents, each of them differing in their system intelligence and input modality, as personal assistants for Mediated Atmospheres, an adaptive smart office prototype. They were evaluated in a user study (N=33) to collect subjective and objective measures. Results showed that a smartphone application was the most favorable system, followed by conversational text and voice agents that were perceived as being more engaging and intelligent than a non-conversational voice agent. Significant differences were observed between native and non-native speakers in both subjective and objective measures. Our findings reveal the potential of conversational agents for the interaction with adaptive environments to reduce work and information overload.
Keywords: ubiquitous computing; smart office; conversational agents; smart agents; chatbot; human–computer interaction; adaptive environments; multimodal interaction; mediated atmospheres